2021
DOI: 10.48550/arxiv.2111.07925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NGC 1850 BH1 is another stripped-star binary masquerading as a black hole

Kareem El-Badry,
Kevin Burdge

Abstract: We show that the radial velocity-variable star in the black hole candidate NGC 1850 BH1 cannot be a normal ∼ 5 𝑀 subgiant, as was proposed, but is an overluminous stripped-envelope star with mass ∼ 1𝑀 . The result follows directly from the star's observed radius and the orbital period -density relation for Roche lobe-filling stars: the star's density, as constrained by the observed ellipsoidal variability, is too low for its mass to exceed ∼ 1.5 𝑀 . This lower mass significantly reduces the implied mass of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Their evolutionary history is qualitatively quite similar to the models explored to explain the HR 6819, LB-1, and NGC 1805 BH1 systems (e.g. Eldridge et al 2020;Bodensteiner et al 2020b;El-Badry & Quataert 2021;El-Badry & Burdge 2021;Stevance et al 2021). In all the selected models, mass transfer begins while the donor is still on the main sequence ("case A").…”
Section: Bpass Library Searchsupporting
confidence: 58%
See 1 more Smart Citation
“…Their evolutionary history is qualitatively quite similar to the models explored to explain the HR 6819, LB-1, and NGC 1805 BH1 systems (e.g. Eldridge et al 2020;Bodensteiner et al 2020b;El-Badry & Quataert 2021;El-Badry & Burdge 2021;Stevance et al 2021). In all the selected models, mass transfer begins while the donor is still on the main sequence ("case A").…”
Section: Bpass Library Searchsupporting
confidence: 58%
“…All of these systems were initially interpreted as containing a main-sequence B star orbiting a black hole, but subsequent studies (e.g. Irrgang et al 2020;Shenar et al 2020;Bodensteiner et al 2020b;El-Badry & Quataert 2021;El-Badry & Burdge 2021) have shown that the B stars are not on the main sequence, but appear to be undermassive (β‰ˆ 0.5βˆ’1.5 𝑀 ) stripped products of binary evolution that are currently contracting to become core helium burning sdOB stars. Because the current evolutionary state of these objects is short-lived, their discovery implies that there may be many other systems with similar evolutionary histories yet to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The mass function yields a Roche radius of approximately 10 R , giving a fill factor of only 0.66. This system cannot reproduce the observed light curve as it would generate maximum (i.e., sini=1) ellipsoidal light variations with an amplitude of only ∼4-5%, significantly smaller than the observed light curve constraint of ∼10-12%, in broad agreement with El-Badry & Burdge (2021). Reducing the mass of the primary we find that its Roche radius matches the stellar radius for a mass of ∼1.8 M , the light curve then implying i∼47Β°with a BH mass of ∼5.8 M .…”
Section: Conclusion and Caveatsmentioning
confidence: 47%
“…Given that these systems can be well described by models in which an undermassive stripped star orbits a Be star (e.g. Shenar et al 2020;Bodensteiner et al 2020;El-Badry & Burdge 2021), it is worth considering carefully whether such a scenario could also explain NGC 2004 #115. An attractive feature of the stripped star scenario is that it simultaneously explains the slow rotation of the B star and the rapid rotation of the Be star.…”
Section: Is a Stripped Star Scenario Possible?mentioning
confidence: 99%